2020
DOI: 10.17794/rgn.2020.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Types and Distribution of Quaternary Deposits Originating From Carbonate Rock Slopes in the Vinodol Valley, Croatia – New Insight Using Airborne Lidar Data

Abstract: The Vinodol Valley, situated in the north-western Adriatic in Croatia, is characterized by complex geological and morphological conditions. Palaeogene flysch deposits form the inner parts of the valley, while the steep valley flanks are composed of Cretaceous and Palaeogene carbonate rocks. Flysch bedrock is mostly covered by diverse Quaternary deposits, among which deposits originating from carbonate rock slopes are abundant. During previous investigations, based on conventional field geological mapping and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The rock fragment in the soil is a product of weathering and disintegration of rocks; rock fragments may be produced in chemical weathering and root penetration processes that transform rocks into soil [ 53 ]; tectonic movement [ 54 ]; physical weathering, landslides, and debris flows [ 55 ]; and water selective erosion of soil fine particles [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rock fragment in the soil is a product of weathering and disintegration of rocks; rock fragments may be produced in chemical weathering and root penetration processes that transform rocks into soil [ 53 ]; tectonic movement [ 54 ]; physical weathering, landslides, and debris flows [ 55 ]; and water selective erosion of soil fine particles [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in many landslide susceptibility assessments, stratigraphic units presented in geological maps are aggregated and used to describe rock characteristics [66], that is, forming engineering geological formations. Therefore, engineering geological formations were additionally mapped using LiDAR DTM derivatives to modify the geological contact, according to a suggestion by [67,68]. The suggested methodology demonstrated efficacy in forested areas and resulted in an engineering geological map.…”
Section: Deriving Input Data Layers For Landslide Conditioning Factor...mentioning
confidence: 99%
“…Airborne LiDAR is valuable for road design on slopes and in hilly areas. In their study, P. Jagodnik et al [81] discovered that the type and shape of soil geological engineering properties can be integrated to detect gravitational mass movement and rockfall occurrence from mapping using a visual interpretation from LiDAR. In comparison, R. Pellicani et al [82] and D. Gadone et al [83] identified characteristics of soil failure signals and hence detected soil instability by mapping from LiDAR.…”
Section: Designing Roads On Slopse and In Hilly Areasmentioning
confidence: 99%